Opportunities for speaking: the if, how and when of students’ spoken target language in the second foreign language classroom - Nyström, Fredrika (Moderna Språk, 2025)
The present study investigates spoken target language in Spanish classes within Swedish lower secondary schools. In spite of the communicative goals of foreign languages, speaking is the least investigated skill and the investigation contributes with insights into the contexts when the target language is spoken in Modern language class. Twenty-one lessons in five different classrooms were audio- and video-recorded, then analysed using a tool developed specifically for the present study, the Revised speaking observation scheme. In this scheme the students’ spoken language was in focus and explicitly separated from the teachers’ language. The findings show that students mostly spoke the target language during activities when they were encouraged or requested to do so, and not used it as the regular means of communication. When scaffolding structures were available, the students used them in their own production, and speaking completely without scaffolding was rare. Moreover, the classroom activities involving spoken target language were placed on a communicative continuum and could be categorised as either triggering language practice or language use. Hence, the results suggest a need for more explicit spoken language activities during class, scaffolded in a way that enables the students to perform them.